2012
DOI: 10.1038/embor.2012.116
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic thioredoxin system facilitates the import of mitochondrial small Tim proteins

Abstract: Thiol-disulphide redox regulation has a key role during the biogenesis of mitochondrial intermembrane space (IMS) proteins. Only the Cys-reduced form of precursor proteins can be imported into mitochondria, which is followed by disulphide bond formation in the mitochondrial IMS. In contrast to the wealth of knowledge on the oxidation process inside mitochondria, little is known about how precursors are maintained in an importcompetent form in the cytosol. Here we provide the first evidence that the cytosolic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 28 publications
0
20
0
2
Order By: Relevance
“…Other studies have shown the importance of redox systems for the import of mitochondrial proteins into the IMS. Loss of yeast thioredoxins leads to reduced import rates and accumulation of oxidized unimported pre-proteins (Durigon et al., 2012). However, the IMS localization of thioredoxin could provide an alternative explanation, since Trx1 may be responsible for maintaining the redox environment in the IMS, as well as providing the reducing power for Gpx3.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown the importance of redox systems for the import of mitochondrial proteins into the IMS. Loss of yeast thioredoxins leads to reduced import rates and accumulation of oxidized unimported pre-proteins (Durigon et al., 2012). However, the IMS localization of thioredoxin could provide an alternative explanation, since Trx1 may be responsible for maintaining the redox environment in the IMS, as well as providing the reducing power for Gpx3.…”
Section: Discussionmentioning
confidence: 99%
“…A second model is based on our recent finding that the cytosolic Trx system facilitates the import of mitochondrial small Tim proteins [14]. Thioredoxins and glutaredoxins (Grx) are ubiquitous oxidoreductases in charge of thiol regulation and oxidative stress defense.…”
Section: Keeping the Precursor Protein Reduced And Unfolded In Thementioning
confidence: 99%
“…Durigon et al . [14] recently showed that a Δ trx1trx2 double deletion mutant has a strong growth defect under respiratory conditions. The mutant strain also has lower mitochondrial levels of the small Tim proteins.…”
Section: Keeping the Precursor Protein Reduced And Unfolded In Thementioning
confidence: 99%
See 2 more Smart Citations